Analysis of XCMG's Capital Return Payment Capability from the Perspective of Free Cash Flow - Qinzhao Luo; Yuqiang Chen; HaoJie Liao; Kangqiao Xu (Journal of Frontier in Economic and Management Research, 2025)
This study investigates the dynamic evolutionary trajectory of XCMG's capital return payment capacity through the lens of free cash flow (FCF), leveraging the company’s financial data spanning the period from 1998 to 2024. By integrating free cash flow metrics with indicators of debt-servicing capability and profit quality, the research conducts a systematic analysis of the core determinants that shape the firm’s ability to meet capital return obligations. The findings reveal that both FCF1 and FCF2 of XCMG exhibit pronounced cyclical volatility; moreover, the rigid growth of interest expenses has the effect of amplifying cash flow gaps, which in turn renders the capital return payment capacity highly sensitive to external financing sources during periods of industry downturn. In light of these results, the paper puts forward a set of recommendations, including the compression of leverage ratios, the optimization of investment pacing, and the strengthening of cash recovery mechanisms, with the aim of providing empirical evidence to support the construction machinery industry in enhancing free cash flow creativity and realizing high-quality development